2003
DOI: 10.1063/1.1537052
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorescent top-emitting organic light-emitting devices with improved light outcoupling

Abstract: A dielectric capping layer has been used to increase the light output and to tune the spectral characteristics of top-emitting, phosphorescent organic light-emitting devices (OLEDs). By controlling the thickness of the dielectric layer deposited on top of a thin metal cathode, the transmittance of the top electrode can be adjusted. Maximum light output is not achieved at highest cathode transmittance, indicating that the interplay between different interference effects can be controlled by means of the capping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
147
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(150 citation statements)
references
References 13 publications
2
147
1
Order By: Relevance
“…In recent years there have been many reports of glass-based top-emissive OLEDs with good performance where Ag, 7,8 Al/Ag, 9,10 LiF/Al 12 and LiF/Al/Ag [12][13][14][15][16] have been applied as the transparent cathode, often in combination with a capping layer such as N,N'-bis(naphthalen-1-yl)-N,N'-bis(phenyl)-benzidine (NPB), [10][11][12][13][14][15][16][17] N,N,N',N'-tetrakis(4-methoxyphenyl)benzidine (MeO-TPD), 9 tris(8-hydroxyquinolinato)aluminium (AlQ3) 3 , 17,18 tin-doped indium oxide (ITO), SiO 2 , 15 or ZnSe. 16,19 With this second metal electrode, a microcavity resonator is obtained that amplifies a specific wavelength range and particular emission angles 15,20,21 (acting like a Fabry-Pérot filter). As a result, spectral narrowing and an increased angle dependence of the electroluminescence are obtained, which are hard to optimize simultaneously.…”
Section: Top-emissive Oleds On Metal Foilmentioning
confidence: 99%
“…In recent years there have been many reports of glass-based top-emissive OLEDs with good performance where Ag, 7,8 Al/Ag, 9,10 LiF/Al 12 and LiF/Al/Ag [12][13][14][15][16] have been applied as the transparent cathode, often in combination with a capping layer such as N,N'-bis(naphthalen-1-yl)-N,N'-bis(phenyl)-benzidine (NPB), [10][11][12][13][14][15][16][17] N,N,N',N'-tetrakis(4-methoxyphenyl)benzidine (MeO-TPD), 9 tris(8-hydroxyquinolinato)aluminium (AlQ3) 3 , 17,18 tin-doped indium oxide (ITO), SiO 2 , 15 or ZnSe. 16,19 With this second metal electrode, a microcavity resonator is obtained that amplifies a specific wavelength range and particular emission angles 15,20,21 (acting like a Fabry-Pérot filter). As a result, spectral narrowing and an increased angle dependence of the electroluminescence are obtained, which are hard to optimize simultaneously.…”
Section: Top-emissive Oleds On Metal Foilmentioning
confidence: 99%
“…There have been several works on calculating the emission pattern [5] and external coupling in OLEDs [6]. It has been shown that the emission from an OLED can be varied through interference effects by changing the thickness of the organic layer in an OLED with a dielectric layer located below the ITO anode [7] or by changing the thickness of a ZnSe layer on top of the metal cathode [8][9]. For an OLED with SiO 2 layer below the ITO, it was shown that the emission spectrum from an OLED is strongly dependent on the Alq 3 thickness, so that with the increase of Alq 3 thickness the emission peak shifts from ~525 nm to ~555 nm, and with further increase of the thickness even splits into two peaks, one located ~495 nm and the other ~590-600 nm [7].…”
Section: Introductionmentioning
confidence: 99%
“…For modeling of these two effects we use an ensemble of incoherent electrical dipole antennas with random orientation, 6,7 used in earlier work. [8][9][10][11] It is assumed that the OLED is a one-dimensional layer structure since its lateral dimensions (>1 mm) are much larger than its thickness ($1 lm). The emission of the dipole antenna is decomposed in plane and evanescent coherent waves with a transverse electric (TE) and transverse magnetic (TM) polarization.…”
Section: A External Quantum Efficiency (Eqe)mentioning
confidence: 99%